Horses for Courses in the Era of CARs: Advancing CAR T and CAR NK Cell Therapies - Sergey Kulemzin (MDPI AG, 2021)
The adoptive transfer of allogeneic CAR NK cells holds great promise as an anticancer modality due to the relative ease of manufacturing and genetic modification of NK cells, which translates into affordable pricing. Compared to the pronounced efficacy of CAR T cell therapy in the treatment of B cell malignancies, rigorous clinical and preclinical assessment of the antitumor properties of CAR NK cells has been lagging behind. In this brief review, we summarize the biological features of NK cells that may help define the therapeutic niche of CAR NK cells as well as create more potent NK cell-based anticancer products. In addition, we compare T cells and NK cells as the carriers of CARs using the data of single-cell transcriptomic analysis.